Designing The Concepts - The Maturity Level of Career Development Smart Pondok Pesantren (Islamic Boarding Schools) - Sendi Novianto; Indra Gamayanto; Sasono Wibowo (International Journal Ihya' 'Ulum al-Din, 2022)
In the face of globalization, Islamic boarding schools require rapid change and development, especially in careers, and contribute to society and the boarding school. Therefore, we need a concept to build a career properly and how a contribution can be helpful in stages. Problems such as human resource development are necessary so that Islamic boarding schools can positively impact people worldwide. This article is an extension of previously published essays and the method used. Moreover, this article's result is a valuable career development framework for increasing human resource competence, detailed job descriptions, and how contributions can make gradual so that they are right on target. This framework and process will be very useful in increasing ability and teamwork. It also needs to be done so that Islamic boarding schools can develop rapidly; of course, it is also necessary to have consistency in implementing this to create high competency human resources as proof that this concept implemented is that we have carried out community service by implementing cloud storage as a medium for registering new students at the Askhabul Kahfi Islamic boarding school and have made the Si-PenO (Online registration information system) application. Of course, these two things will continue to develop so that Islamic boarding schools can increase their competence and competitiveness in the face of globalization.